Simultaneous enhancement on lignin degradation and methane production from anaerobic co-digestion of waste activated sludge and alkaline lignin supplemented with N2-nanobubble water. (September 2020) - Yang, Xiaojing; Nie, Jingmin; Wei, Yu; Zhao, Ziwen; Shimizu, Kazuya; Lei, Zhongfang; Zhang, Zhenya
Abstract: Lignin with highly complex aromatic hydrocarbons is recalcitrant to biodegradation. Hydroxyl radical (OH) plays a vital role in lignin depolymerization, which can be generated from nanobubble water (NBW). This study focused on evaluating the effect of nitrogen gas NBW (N2 -NBW) on lignin degradation and methane production via anaerobic co-digestion (AcoD) of waste activated sludge (WAS) and alkaline lignin. The results showed that total methane yield was obviously increased by 17% under N2 -NBW addition, which followed a dose-dependent manner. Volatile fatty acids (VFAs) production and consumption in addition to volatile solids (VS) reduction were enhanced during the AcoD process supplemented with N2 -NBW. Lignin degradation rate was improved by 10% under N2 -NBW addition condition compared to the control at an initial lignin concentration of 50 mg/L. It's hypothesized that OH generated by NBW can facilitate lignin degradation and bioenergy conversion. Graphical abstract: Unlabelled Image Highlights: Effect of NBW on lignin degradation via AcoD with WAS was studied. N2 -NBW promoted both total methane production (17%) and lignin degradation (10%). Enhancement effect of N2 -NBW addition followed a dose-dependent manner. CH4 yield and lignin degradation decreased with elevated lignin concentration.